The role of monetary policy in developing countries : theoretical perspective and institutional framework - Sisay, S. S.; Economic Research Department of the Central Bank of The Gambia (Banjul, Gambia : Central Bank of The Gambia, 1978)
The symposium proved to be a useful forum for the exchange of views on the role of monetary policy and the high standard of the papers presented during the two-day session was reflected in the lively discussions which followed every contribution.
Symposium held in Banjul, The Gambia on 20th and 21st February 1978.
Includes bibliographical references.
osc 09/04/2019
Loans
Keywords: Monetary policy; Central banking; Gambia